Temporal and Spatial Dynamics of Volcanic Aerosols: Absorbing Aerosol Index (AAI) Analysis During the Eruption of Mount Lewotobi Laki-laki - Khusnani, Azmi; Jufriansah, Adi; Wahab, Dedi Suwandi; Samana, Fazaki Ramadhani Anwar; Bahruddin, Sitti Arafah; Anwar, Zaina; Nursilawati, Wingki; Arifin, Anggun Syafira (Jurnal Penelitian Sains Teknologi, 2026)
In November 2024, the eruption of Mount Lewotobi Laki-laki on Flores Island, Indonesia, resulted in the release of substantial volcanic aerosols, including sulfur dioxide (SO₂) and volcanic debris. These aerosols impacted the environment, health, and aviation activities. The objective of this investigation is to examine the temporal and spatial dynamics of volcanic aerosols by employing the Absorbing Aerosol Index (AAI) in conjunction with TROPOMI satellite data (Sentinel-5P). The methodologies employed are as follows: spatial-temporal analysis with Google Earth Engine (GEE), aerosol dispersion simulation with the HYSPLIT model, and data processing with the Sentinel Application Platform (SNAP). The results indicated a substantial increase in volcanic activity from November 8th to 11th, 2024, as evidenced by an ash column that reached a height of as much as 10,945 m. The distribution of aerosols was influenced by atmospheric dynamics, with high concentrations observed in the vicinity of Mount Lewotobi Laki-laki and extending to the east-southeast. Although the level of volcanic activity declined in late November, aerosol concentrations were still detected in the atmosphere. This investigation offers critical insights into the distribution of volcanic aerosols during the eruption and its effects on disaster risk mitigation and air quality. It is anticipated that these discoveries will facilitate the implementation of more sustainable and effective risk management strategies for volcanic eruptions.